Homepage Usability: Multiple Case Studies Of Top 5 IPTA’S Homepage In - Ahmad, Ahmad Khairul Azizi; Abdullah, Anwar Fikri; Ibrahim, NurHisham (2016)

(untitled)
Generally, all universities have a website that has information about the background of the universities and other sub menus that are related to the universities. The website owners should know their websites’ usability level in order to deliver messages effectively. This research has intended to identify the importance of the usability factor in the creation of a website. This research has employed a survey method that has been used to analyse the data to identify the crucial aspects that need to be fulfilled and followed before embarking on a homepage design process. This survey has evaluated the top 5 local universities in Malaysia, which are Universiti Malaya (UM), UniversitiKebangsaan Malaysia (UKM) UniversitiTeknologi Malaysia (UTM), UniversitiSains Malaysia (USM) and Universiti Putra Malaysia (UPM). The evaluation of the usability factor involved were ease of use, navigation, graphics, layout, text and font size. This research is very important, considering the lack of local academic writings regarding homepage usability that are being produced as a guide in the creation of websites. Interview sessions with local professional webpage designers were carried out to get their views, visions and aspirations in webpage designs for universities. The results have been compared in order to fulfil the research objective. The data collection was acquired verbally as well as visually. The findings can be used as a reference to set certain standards in webpage design and creation, and also to be used for academic benefits